Threats to the individual’s right to privacy in relation to processing of personal data in order to prevent and combat crime (Ius Novum, 2020)
The article contains an analysis of the regulation concerning the protection of personal data processed in relation to the prevention and combating of crime from the perspective of solutions contained in Directive 2016/680 of the European Parliament and of the Council of 27 April 2016 on the protection of natural persons with regard to the processing of personal data by competent authorities for the purposes of the prevention, investigation, detection or prosecution of criminal offences or the execution of criminal penalties, on the free movement of such data, and repealing Council Framework Decision 2008/977/JHA (OJ L 119, p. 89), taking into account civil liberties. The EU regulation of personal data protection in the area of police and judicial cooperation in criminal matters raises the question of the scope of permissible interference of state authorities in the right to privacy. In this article, the author assesses the new assumptions ensuring transparency of data processing by the police and institutions fighting crime from the point of view of confidentiality guarantees related to data processing in proceedings conducted by competent authorities in this area.
Keywords: right to privacy; personal data; crime; police and judicial cooperation